Patriarchal Norms and Women Access to Reproductive Healthcare Services in Benin City, Nigeria - Omigie, Sunday Oseye; Uwagbale, Raymond Francis (NIU Journal of Social Sciences, 2025)
This study examined the effect of patriarchal norms on women access to reproductive healthcare services in Benin City, Edo State. The specific objectives are to assess the degree to which patriarchal norms influence women’s autonomy in making decisions about reproductive healthcare in Benin City, Edo State; to determine the main barriers associated with patriarchal norms that restrict women’s access to reproductive healthcare services in Benin City and to investigate how women and men perceive the influence of patriarchal norms on women’s reproductive health outcomes in Benin City.The population for this inquiry encompasses women within the reproductive age bracket (15-55 years) who reside in Benin City. Also married men were allowed to participate in this study. and the sample size of this study was 100 respondents and random sampling technique was adopted to select the respondents. The study adopted descriptive statistics (frequency, percentages and tables) and inferential statistics (p-value, t-value, F-statistics and Levene's Test) as its major statistical tools for data analysis. The analysis established that  patriarchal norms has significant effect on autonomy of women in making decisions concerning reproductive healthcare in Benin City, Edo State and that no significant difference exists in perceptions between women and men concerning patriarchal norms' role in women’s reproductive health outcomes in Benin City.Finally, the study recommends that there should be community engagement by engaging men and community leaders in educational programmes to challenge patriarchal norms and promote shared reproductive health decision-making and that there should be policy and legal reforms to Strengthen legal frameworks to ensure women's reproductive rights and autonomy, while tackling socioeconomic and political inequalities that impede care access. Keywords: Patriarchal Norms, Reproductive Healthcare, Women’s Autonomy, Decisions Making.